Model of Development and Organization of Curriculum Islamic Religious Education - Lutfil Hakim; A. Badaruddin; Mohammad Asrori (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the development of Islamic religious education curriculum organization in Indonesia. Ideally, every educational institution makes a curriculum that is relevant to the conditions and needs of the community. The type of research used is qualitative with literature study. Data sources are obtained from articles, books, websites that contain the development of the Islamic religious education curriculum organization. Data analysis used in this research is content analysis method. After analyzing the data, the results obtained are: there are four developments in the organization of Islamic education curriculum, namely separate subject curriculum, correlated curriculum, unified curriculum, and integrative thematic curriculum. However, the relevant organization for PAI in the present is the integrated thematic curriculum. Because the curriculum trains students in problem solving, hands-on learning opportunities, and provides space for students to develop their talents.